Internet browsing and Web 2.0 Competencies as Correlate of Effective Management of Institutional Repository by Librarians in Federal Universities in South-South, Nigeria - Robinson , Janet Nnenta; Ukaegbu, Bernadette C. N. (Indonesian Journal of Data and Science, 2024)
This study was carried out to investigate Internet browsing and Web 2.0 competencies as correlate of effective management of institutional repository by Librarians in federal universities in South-South, Nigeria. Utilizing a correlational design, the study answered three questions and tested three hypotheses. The cohort of 242 Librarians from seven federal universities—115 academic and 127 non-academic—constituted the study's population. A stratified total census sampling approach was deployed to include all 242 librarians. Data gathering utilized two questionnaires: the "Librarian Internet Browsing and Web 2.0 Competencies Questionnaire (LIBWCQ)" and the "Effective Management of Institutional Repositories Questionnaire (EMIRQ)". Both tools were validated for face and content by experts and yielded Cronbach Alpha reliability coefficients of 0.75 and 0.77, respectively. Mean scores addressed the research questions, while regression analysis tested the hypotheses at a significance level of 0.05. Results indicated a 52% joint correlation between the Librarians' web competencies and effective management of repositories, notably in activities like social media engagement and collaboration with faculty and students using the digital space. The study concluded and recommended that Librarians should bolster their digital skills through professional development initiatives, such as workshops, webinars, and conferences, focusing on digital management and Web 2.0 tool application to keep up-to-date with technological advancements and best practices in management of institutional repository.